Genome Sequencing Explores Complexity of Chromosomal Abnormalities in Recurrent Miscarriage - Dong, Zirui (Am J Hum Genet, 2019)
Recurrent miscarriage (RM) affects millions of couples globally, and half of them have no demonstrated etiology. Genome sequencing (GS) is an enhanced and novel cytogenetic tool to define the contribution of chromosomal abnormalities in human diseases. In this study we evaluated its utility in RM-affected couples. We performed low-pass GS retrospectively for 1,090 RM-affected couples, all of whom had routine chromosome analysis. A customized sequencing and interpretation pipeline was developed to identify chromosomal rearrangements and deletions/duplications with confirmation by fluorescence in situ hybridization, chromosomal microarray analysis, and PCR studies. Low-pass GS yielded results in 1,077 of 1,090 couples (98.8%) and detected 127 chromosomal abnormalities in 11.7% (126/1,077) of couples; both members of one couple were identified with inversions. Of the 126 couples, 39.7% (50/126) had received former diagnostic results by karyotyping characteristic of normal human male or female karyotypes. Low-pass GS revealed additional chromosomal abnormalities in 50 (4.0%) couples, including eight with balanced translocations and 42 inversions. Follow-up studies of these couples showed a higher miscarriage/fetal-anomaly rate of 5/10 (50%) compared to 21/93 (22.6%) in couples with normal GS, resulting in a relative risk of 2.2 (95% confidence interval, 1.1 to 4.6). In these couples, this protocol significantly increased the diagnostic yield of chromosomal abnormalities per couple (11.7%) in comparison to chromosome analysis (8.0%, chi-square test p = 0.000751). In summary, low-pass GS identified underlying chromosomal aberrations in 1 in 9 RM-affected couples, enabling identification of a subgroup of couples with increased risk of subsequent miscarriage who would benefit from a personalized intervention.